FLOTATION PROCESSES DURING THE CONSTRUCTION WORKINGS-TANKS BY UNDERGROUND DISSOLUTION OF ROCK SALT WITH A HIGH CONTENT OF GAS - V P Malyukov; Y I Starovoytova (RUDN Journal of Engineering Research, 2017)
Analyzed experimental and field studies of flotation processes in the construction of mines-tanks for backup of hydrocarbons by the method of underground dissolution of rock salt with a high content of gas.